An Alarmingly High Proportion of HIV-1 Isolates Carrying Mutations Corresponding to Resistance to Antiretroviral Drugs among HIV-Positive High-Risk Groups in Central Vietnam: a Substudy of the National Sentinel Survey - Do, Hung Thai; Nguyen, Dong Thanh; Nguyen, Lan Anh Thi; Do, Duong Huy; Le, Huy Xuan; Trinh, Xuan Mai Thi; Ton, Hong Vy Nu; Sawada, Ikumi; Kitamura, Noriko; Le, Minh Nhat; Yoshihara, Keisuke; Phan, Thu Huong Thi; et al. (Japanese journal of infectious diseases, 2017)
We studied the prevalence of HIV drug resistance among high-risk groups such as injecting drug users (IDUs), female sex workers (FSWs), and men having sex with men (MSM) in central Vietnam. We used HIV-positive blood samples from 2012-2013 sentinel surveillance surveys. Study subjects were screened for HIV infection by standardized screening assays, and the HIV-positive samples were further tested for HIV viral load and drug-resistance mutations (DRMs) by in-house assays. DRMs were identified using the Stanford University online sequence analysis tool. Their risk behaviors were also investigated. During the study period, 6,016 (high-risk) subjects were screened, and 97 tested positive for HIV infection (IDUs: n = 63, 3.0%; FSWs: n = 24, 0.9%; and MSM: n = 10, 1.0%). Ninety-two of the 97 samples (45 from 2012 and 47 from 2013) were available for further testing. HIV RNA was detected in 56 (60.9%) of the 92 samples, and drug resistance genotyping was successfully performed on 40 (71.4%) samples. All these isolates were subtype CRF01_AE, except for 1 (2.5%) IDU whose HIV belongs to subtype B. Thirteen individuals (32.5%) were carrying HIV with at least 1 DRM: 9 IDUs, 1 FSW, and 3 MSM. Thus, HIV seroprevalence among high-risk individuals in central Vietnam is low, but a high proportion of drug resistant HIV-1 isolates is observed in the high-risk group.